PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN JASA PENGIRIMAN JNE DI MERAUKE - Irfan Wildzan Muafa (Musamus Journal of Business & Management, 2018)
This research was conducted to find out how far the influence of price and service quality on customer satisfaction in selecting and using JNE branch Merauke freight forwarding services. The sample used in this study was 88 respondents. This study uses multiple linear regression analysis techniques. The results of the data processing using the SPSS 22 program found the equation Y = 0.256 X1 + 0.228 X2 + e. From the results of the t test and F test, it can be seen that the price and service quality variables have a positive and significant effect on customer satisfaction in JNE shipping services. This is evidenced by the results of the tcount variable price (X1) 3,059 with t table 1.6623 with a significance of 0.003 <0.05. With the direction of the positive coefficient, it is thus obtained that the hypothesis which states that prices have a significant positive influence on customer satisfaction is acceptable. The results of tcount variable service quality (X2) 3.752 with ttable 1.6623 with a significance of 0,000 <0.05. With the direction of a positive coefficient, it is thus obtained that the hypothesis which states that service quality has a significant positive influence on customer satisfaction is acceptable. The regression calculation results can be seen that the coefficient of determination (adjusted R2) obtained is 0.406. This means that 40.6% of patient satisfaction can be influenced by price and service quality and 59.4% other satisfaction can be influenced by other variables. Keywords: Price, Service Quality, Customer Satisfaction